Plasma aminotransferase concentrations in preterm infants. Issue 2 (1st July 2009) - Victor, S; Dickinson, H; Turner, M A
Abstract : The aim of this study was to generate reference ranges for aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in preterm infants by describing the observed plasma concentration of these enzymes in babies born between 22 and 36 weeks' gestation. A service evaluation was conducted in babies admitted to two large neonatal intensive care units in the UK. 7006 blood samples from 1860 infants admitted to the two units between 2004 and 2008 were included. Extremely premature infants had high plasma enzyme activities when compared to babies at a later corrected gestational age. This may be due to more severe illness immediately after birth.